Identity Styles and Religiosity: Examining the Role of Identity Commitment. Issue 2 (3rd May 2016) - Grajales, Tevni E.; Sommers, Brittany
ABSTRACT: This study observed the role of identity styles, identity commitment, and identity statuses in predicting religiosity in a sample of undergraduate students attending a Seventh-day Adventist university ( N  = 138). Two structural models were evaluated via path analysis. Results revealed two strong models for the prediction of religiosity. Identity styles explained 24% of the variance in religiosity, with the relationship mediated by identity commitment. Religious identity status explained 56% of the variance in religiosity, with the relationship not mediated by identity commitment. Implications of these interactions for understanding religious identity development are discussed.